2017
DOI: 10.1159/000475746
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Salvianolate on Contrast-Induced Nephropathy after Primary Percutaneous Coronary Intervention: A Prospective Multicenter Randomized Controlled Trial

Abstract: Objectives: This study's aim was to evaluate the protective effects of salvianolate on contrast-induced nephropathy after primary percutaneous coronary intervention (PPCI) compared with normal saline (NS) hydration. Methods: We enrolled patients with acute myocardial infarction who underwent PPCI in 3 centers in Shanghai. The patients were randomly assigned to the salvianolate group or the NS group. The incidence of CIN, the changes in renal function parameters, and the occurrence of adverse events after the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…We tested salvianolate with 200mg daily for total three days in our study. In a previous study, seven days of salvianolate infusion with 400mg daily can protect contrast-induced nephropathy after PCI [15]. Another study with 400mg daily for 7 days can attenuate microvascular dysfunction after cardiac ischemia and reperfusion which showed smaller infarct size and improved left ventricular systolic function [5].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We tested salvianolate with 200mg daily for total three days in our study. In a previous study, seven days of salvianolate infusion with 400mg daily can protect contrast-induced nephropathy after PCI [15]. Another study with 400mg daily for 7 days can attenuate microvascular dysfunction after cardiac ischemia and reperfusion which showed smaller infarct size and improved left ventricular systolic function [5].…”
Section: Discussionmentioning
confidence: 95%
“…Salvianolate is extracted from Salvia miltiorrhiza which contains magnesium lithospermate B, rosmarinic acid and lithospermic acid [14][15][16]. Salvianolate treatment showed less severe myocardial injury or myocardial infarction after PCI via its diverse pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] It can also reduce the incidence of contrast-induced nephropathy after PCI and is more effective than normal saline. [ 15 ] In addition, it has been confirmed that intravenous administration of salvianolate can improve cardiac microcirculatory perfusion and increase cardiac output in rats. [ 16 ] Similarly, continuous intravenous salvianolate 10 mg/kg/day for 7 days can significantly improve myocardial microcirculatory reflow in an ischemia-reperfusion minipig model, as well as reduce oxidative stress and myocardial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Adoption of primary PCI strategy has resulted in signi cant improvement in outcomes of patients with STEMI, (3) however, risk of contrast-induced acute kidney injury (CI-AKI), also called contrast induced nephropathy (CIN), remains high in these patients with the reported incidence rate ranging from 5.5-21.6% in various studies depending on de nition used for the categorization of CIN and inclusion criteria. (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) CIN is found to be associated with increased risk of need for dialysis and mortality, (16) chronic kidney disease (CKD) followed by CIN in these patients, is found to be associated with increased risk of long term adverse outcomes. (21) In the recent years, several studies have been performed evaluating various risk strati cation tools and biomarkers in the context of CIN after primary PCI which included Mehran risk score (MRS), (7,17) plasma N-terminal pro-brain natriuretic peptide (NT-proBNP), (7,18) gamma-glutamyl transferase (GGT), (20) thrombolysis in myocardial infarction risk index (TRI), (8) PRECISE-DAPT risk score, (10) Canada Acute Coronary Syndrome (C-ACS) score, (11) fragmented QRS complexes (fQRS), (12) and combination of various other tools.…”
Section: Introductionmentioning
confidence: 99%